2019
DOI: 10.1038/s41550-018-0661-3
|View full text |Cite
|
Sign up to set email alerts
|

A new class of flares from accreting supermassive black holes

Abstract: Accreting supermassive black holes (SMBHs) can exhibit variable emission across the electromagnetic spectrum and over a broad range of time-scales. The variability of active galactic nuclei (AGN) in the ultra-violet (UV) and optical is usually at the few tens of percent level over time-scales of hours to weeks 1 . Recently, rare, more dramatic changes to the emission from accreting SMBHs have been observed, including tidal disruption events (TDEs) 2-5 , "changing look" AGN 6-9 , and other extreme variability o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
114
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(123 citation statements)
references
References 104 publications
(107 reference statements)
7
114
0
2
Order By: Relevance
“…Nonetheless, broad MgII and Hα emission are detected at all times. We also note that Figure 4 provides evidence for increased O III λ3133 emission in high flux states, which could be produced by Bowen fluorescence (Trakhtenbrot et al 2019b luminosity L (erg s 1 ) 57100 57600 58100 MJD Figure 3. Host galaxy subtracted, rest frame, optical to X-ray SEDs.…”
Section: Broad Emission Line Responsementioning
confidence: 86%
“…Nonetheless, broad MgII and Hα emission are detected at all times. We also note that Figure 4 provides evidence for increased O III λ3133 emission in high flux states, which could be produced by Bowen fluorescence (Trakhtenbrot et al 2019b luminosity L (erg s 1 ) 57100 57600 58100 MJD Figure 3. Host galaxy subtracted, rest frame, optical to X-ray SEDs.…”
Section: Broad Emission Line Responsementioning
confidence: 86%
“…Two other rapid turn-on events, OGLE17aaj (Gromadzki et al 2019) and ASASSN-17cv/AT 2017bgt (Trakhtenbrot et al 2019), were especially interesting because of the presence of strong He ii λ4686, N iii λ4640, and N iii λ4100 emission. OGLE17aaj and ASASSN-17cv had relatively quick rises to peak brightness over a few months and had UV/optical SEDs that were well fit by T ∼ 10 4 K blackbodies.…”
Section: Asassn-18jd As a Rapid Turn-on Agnmentioning
confidence: 99%
“…The Bowen fluorescence mechanism (Bowen 1934(Bowen , 1935 has been proposed and widely discussed to explain the prominent O III and N III optical emission lines observed in various and diverse astrophysical systems such as planetary nebulae (e.g., Unno 1955;Weymann & Williams 1969), X-ray binary stars (e.g., McClintock et al 1975), and Wolf-Rayet stars (e.g., Crowther 2007). It has also been proposed in the context of supermassive black hole accretion disks by Netzer et al (1985), but only recently identified in a flaring AGN for the first time (Trakhtenbrot et al 2019). Since elements heavier than H and He should be rare in these systems, the only plausible explanation for seeing strong O III and N III fluorescent lines is that these lines are excited by some large sources of energy not available to the predominant H and He.…”
Section: Introductionmentioning
confidence: 99%